VSAT Packet Security Performance Enhancement Using Modified Interlock Protocol - M. Muzzmail, Ayman; Abbas Ali, Hamid; M. Sharif, Sami (University of Khartoum Engineering Journal, 2022)
This study has focused on developing the Interlock protocol and on implementing it on the VSAT system to overcome the man-in-the-middle attack in the double hob topology. A new cryptography protocol has been modified into Interlock protocol by using the concept of Cipher Block Chinning mode and AES, RSA, SAH-256 algorithms. The TCP protocol is flexible and has the ability to tune its parameters depending on the environment under which it works. In this study the TCP protocol parameters had been readjusted to reach the optimum throughput when the packet was encrypted and transmitted in the VSAT environment. The results indicate an increase in the throughput of up to about 30%.